Performance Improvement of Heat Supply Systems Through the Implementation of Wind Power Plants - A. V. Bezhan (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The current growth of energy consumption, which is directly related to the use of a large number of fossil fuels, and, as a result, causes environmental pollution, requires the search for ways to conserve energy and use traditional energy resources economically, as well as to preserve environmental well-being. In such a situation, a good solution to this problem can be the use of energy production technologies based on the use of non-traditional and renewable energy sources, and, in particular, the use of wind energy. In heat supply systems, wind energy can be involved in heat production technologies and then used for heating cities and towns. The method of heat supply of buildings through the use of a combined system of energy sources, consisting of a boiler house and wind power plants, is considered. The methodical basis of a very specific heat supplying system has been developed. The specificity of this system is that the boiler comes into operation, complementing the wind turbine operation, only if the wind is weak or absent at all. In other cases, the heat supply is provided by wind turbines, and the boiler house is waiting for the heating load. An assessment of the possible use of wind power facilities together with a boiler house in providing a heating load schedule for consumers located in an area with an increased potential of the wind which average annual speed is at the level of ~7 m/s is presented. The duration of the heating season in this area is 9–10 months a year. It is shown that the joint use of the boiler house and wind power plants for heat supply purposes during the year can reduce the share of the boiler house in the heat supply of consumers by 50–70 % or more.